2022
DOI: 10.1093/ejo/cjac051
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of quantitative light-induced fluorescence and qualitative visual rating in infiltrated post-orthodontic white spot lesions

Abstract: Summary Objectives The aim of this prospective, clinical single-centre study was to evaluate the masking efficacy of post-orthodontic resin infiltration after 12-month follow-up and correlate quantitative and qualitative outcome measures. Methods Patients with completed fixed orthodontic treatment and the presence of one or more vestibular active non-cavitated white spot lesion/s (WSL) [ICDAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Although the present results showed that polishing neither influenced the caries-protective effect of resin infiltration nor the bacterial adhesion, from a clinical point of view and specially for labial white-spot lesions infiltrated for masking the whitish appearance, it is still probably more reasonable to polish then anyway. Data from previous clinical studies on this application showed that labial lesions may suffer from long-term staining, when not polished 41 43 . Moreover, contrary to the clinical studies on approximal lesions, which all did not report polishing procedures 29 , 44 47 , for labial lesions most of the clinical studies have been performed including polishing steps after light curing of the infiltrant 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the present results showed that polishing neither influenced the caries-protective effect of resin infiltration nor the bacterial adhesion, from a clinical point of view and specially for labial white-spot lesions infiltrated for masking the whitish appearance, it is still probably more reasonable to polish then anyway. Data from previous clinical studies on this application showed that labial lesions may suffer from long-term staining, when not polished 41 43 . Moreover, contrary to the clinical studies on approximal lesions, which all did not report polishing procedures 29 , 44 47 , for labial lesions most of the clinical studies have been performed including polishing steps after light curing of the infiltrant 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the present results showed that polishing neither in uenced the caries-protective effect of resin in ltration nor the bacterial adhesion, from a clinical point of view and specially for labial white-spot lesions in ltrated for masking the whitish appearance, it is still probably more reasonable to polish then anyway. Data from previous clinical studies on this application showed that labial lesions may suffer from long-term staining, when not polished [37][38][39] . Moreover, contrary to the clinical studies on approximal lesions, which all did not report polishing procedures 29,40−43 , for labial lesions most of the clinical studies have been performed including polishing steps after light curing of the in ltrant 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Approval was given by the ethical committee of the RWTH Aachen (EK 110/13). The study design has previously been described in detail and a selection of data referring re-wetting, quantitative analysis of light-induced fluorescence, and qualitative visual rating have been formerly published [13,19]. Reporting follows the STROBE guideline for cohort studies [20].…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%